Evaluation of a Digital Story Pedagogical Module for the Indigenous Learners Using the Stake Countenance Model - Thanabalan, T.V.; Siraj, Saedah; Alias, N. (Elsevier, 2015)
This study involved the development of a literacy pedagogy for the indigenous people in Malaysia. The Developmental Research Approach was used where insights about the indigenous people and their lifestyle were gathered and analysed for content in developing a literacy pedagogical module. Several principles emerged from the data collected and these principles formed the basis for the module. The module encompassing a digital story was implemented in two schools for indigenous students situated in Peninsular Malaysia. The Stake Countenance model was used to analyse and conclude the evaluation of the module. Both teachers and students who participated in the module implementation were directly involved in the evaluation process. Findings showed that there was strong engagement between the Indigenous students and the lessons in the module. The teachers found that the module was able to respond to the needs of the indigenous students. This paper will discuss the evaluation process in detail and present the findings with reference to educational needs of the indigenous students in the country as a whole.